Power-generating footwear based on a triboelectric-electromagnetic-piezoelectric hybrid nanogenerator. (August 2019) - Rodrigues, C.; Gomes, A.; Ghosh, A.; Pereira, A.; Ventura, J.
Abstract: Triboelectric nanogenerators (TENGs) are the most viable solution to harvest energy from low-frequency mechanical motions. Here, a triboelectric nanogenerator, an electromagnetic generator (EMG) and a piezoelectric nanogenerator (PENG) were hybridized and implemented inside a shoe sole to harvest energy from human walking. To optimize the TENG, we developed and studied three different structures (parallel, arcked and zigzag triboelectric plates) based on the contact-separation mode and suitable to be assembled in footwear. The parallel-plate structure generated the largest electrical outputs, so that the distance between triboelectric layers and the number of tribo-pair in this configuration were also optimized. This resulted in a significant increase on the output performance of the TENG and enabled the charging of different capacitors. To further enhance energy generation properties, and through an effective conjugation of triboelectrification, electromagnetic induction and piezoelectricity, we fabricated a hybridized nanogenerator that increased 20% the charging capacity of the TENG system alone. This optimized device opens new horizons for ways to produce and store wasted energy and, in a near future, to power wireless sensors or electronic gadgets. Graphical abstract: Image 1 Highlights: A TENG, an EMG and a PENG were hybridized and implemented inside a shoe sole; TENG was optimized considering 3 different structures to be assembled in footwear. The distance between tribo-layers and the number of tribo-pair were also optimized. The hybridized NG let to an increased the charging capacity of the TENG system alone.